2021
DOI: 10.1080/21655979.2021.1987092
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressing role of serum-derived exosomal microRNA-15a in osteosarcoma cells through the GATA binding protein 2/murine double minute 2 axis and the p53 signaling pathway

Abstract: 2021): Tumor suppressing role of serum-derived exosomal microRNA-15a in osteosarcoma cells through the GATA binding protein 2/murine double minute 2 axis and the p53 signaling pathway, Bioengineered,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Wu et al found that exosomal miR-15a expression decreased in plasma EVs, and exosomal miR-15a was absorbed by OS cells, which suppressed GATA2/MDM2 signaling via the p53 pathway. This inhibited OS cell growth and migration in vitro (104). Major exosome release process in OS.…”
Section: Extracellular Vesicles Are Involved In Osteosarcoma Prolifer...mentioning
confidence: 96%
“…Wu et al found that exosomal miR-15a expression decreased in plasma EVs, and exosomal miR-15a was absorbed by OS cells, which suppressed GATA2/MDM2 signaling via the p53 pathway. This inhibited OS cell growth and migration in vitro (104). Major exosome release process in OS.…”
Section: Extracellular Vesicles Are Involved In Osteosarcoma Prolifer...mentioning
confidence: 96%
“…MiR-15a is located at 13q14.3 of the human genome, and acts as a tumor suppressor in different types of cancers ( Huang et al, 2015 ; Liu et al, 2019a ; Wu et al, 2021 ). In HCC, MSCs-derived exosomes transferred miR-15a to target cells and then suppressed proliferation, migration, and invasion of tumor cells via inhibiting the expression of spalt like transcription factor 4 (SALL4) ( Ma et al, 2021 ).…”
Section: Exosomal Microrna In Osteosarcomamentioning
confidence: 99%
“…Further assays showed that serum-derived exosomes with miR-15a can be internalized by osteosarcoma cells and then miR-15a directly binds to GATA binding protein 2 (GATA2) to inhibit its expression. Since GATA2 can induce the transcription of murine double minute 2 (MDM2) to suppress the p53 signaling pathway, serum-derived exosomal miR-15a can promote apoptosis and cell cycle arrests of osteosarcoma cells via GATA2/MDM2/p53 axis, as demonstrated in Figure 4 ( Wu et al, 2021 ).…”
Section: Exosomal Microrna In Osteosarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…As such, MDM2 has been suggested as a promising target for cancer treatment [ 32 ]. For example, miR-15a suppresses the GATA2/MDM2 axis to inhibit the proliferation and invasiveness of osteosarcoma cells in vitro through the p53 signaling pathway [ 33 , 34 ]. In addition, the aberrant expression of MDM2 was linked to the development of BC [ 34–36 ].…”
Section: Introductionmentioning
confidence: 99%